2001
DOI: 10.1128/aac.45.3.932-935.2001
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of 3-Day Quinine-Clindamycin Treatment versus 7-Day Quinine Treatment for Adult Travelers with Uncomplicated Falciparum Malaria Imported from the Tropics

Abstract: We conducted a randomized, double-blind, placebo-controlled trial to compare a 3-day quinine-clindamycin regimen (group QC) with a 7-day quinine regimen (group Q) for the treatment of uncomplicated Plasmodium falciparum malaria in travelers returning from the tropics. A total of 55 and 53 patients in groups Q and QC were analyzed, respectively. Adverse effects were similar in both groups, although two patients in group Q had severe adverse reactions, leading to the cessation of treatment. The 28-day cure rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 9 publications
1
38
1
Order By: Relevance
“…In vivo, QN is used every 8 h for 7 days, and lack of compliance with this regimen is common (11). Several reports point to a decrease in QN efficacy (1,3,17,24,30,31,34); however, most of these results are based on effectiveness studies. Thus, the observed reduced efficacy could be associated with lack of compliance.…”
Section: Resultsmentioning
confidence: 92%
“…In vivo, QN is used every 8 h for 7 days, and lack of compliance with this regimen is common (11). Several reports point to a decrease in QN efficacy (1,3,17,24,30,31,34); however, most of these results are based on effectiveness studies. Thus, the observed reduced efficacy could be associated with lack of compliance.…”
Section: Resultsmentioning
confidence: 92%
“…A quinine-clindamycin combination was effective against multidrug-resistant malaria in Thailand (20). Furthermore, a 3-day course of clindamycin plus quinine was curative in the treatment of uncomplicated P. falciparum malaria, compared to 7 days of treatment with quinine alone (19). Since clindamycin has been used only for a relatively small number of malaria patients, it is not expected that resistant parasites have developed in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The log-rank test showed that the rate of parasite clearance did not differ in the two arms. on April 8, 2019 by guest http://aac.asm.org/ these patients are similar to those with imported malaria in Europe described previously (8). This study had several limitations.…”
Section: Discussionmentioning
confidence: 82%
“…Newer regimens, including the fixed combinations of atovaquone-proguanil and artemether-lumefantrine, are slowly being introduced, even in the absence of efficacy data from randomized trials with nonimmune subjects. When infections are sensitive to quinine, a 3-day course of quinine and sulfadoxine-pyrimethamine can be given to overcome the problem of poor compliance with longer regimens (4,8,16). Sulfadoxine-pyrimethamine resistance occurs frequently in Southeast Asia and South America and occurs to such an extent that these combinations have questionable efficacies against infections acquired in these areas.…”
mentioning
confidence: 99%